2022
DOI: 10.14739/2310-1210.2022.2.249347
|View full text |Cite
|
Sign up to set email alerts
|

The effect of immunomodulator azoximer bromide on the cytokine profile in a complex therapy for children with newly diagnosed tuberculosis

Abstract: Aim. To analyze the effect of immunomodulator azoximer bromide on the serum cytokine profile (IL-2, IL-6, IL-4, IL-10) in the complex therapy for children with newly diagnosed tuberculosis (TB). Materials and methods. The study included 51 newly diagnosed TB children, who were divided into 2 groups: 26 children received immunomodulator azoximer bromide (main group) in combined therapy with concurrent antimycobacterial therapy (AMBT) and 25 children were assigned to only AMBT (control group). The main group chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…We have found that the use of the immunomodulator azoximer bromide in combined therapy in children with new TB cases after AMBT MF helped to normalize all indicators of the cytokine profile and the balance in the regulatory system of anti-inflammatory cytokines [4].…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…We have found that the use of the immunomodulator azoximer bromide in combined therapy in children with new TB cases after AMBT MF helped to normalize all indicators of the cytokine profile and the balance in the regulatory system of anti-inflammatory cytokines [4].…”
Section: Resultsmentioning
confidence: 90%
“…with new TB cases, alongside normalization of all cytokine profile indicators and the balance in the regulatory system of pro-and anti-inflammatory cytokines [4], helped to achieve by the end of treatment: a shorter average time to culture conversion by 0.9 (1.5 (1.0; 2.0) months against 2.4 (2.0; 3.0) months; P < 0.01), positive radiological dynamics of 77 % (χ 2 = 5.79; P < 0.01), reduced time of destruction healing by 2.1 (1.7 (1.0; 2.0) months against 3.8 (3.0; 4.0) months, P < 0.02), shorter average time of the basic AMBT course by 1.5 (6.2 (5.6; 6.8) months against 7.7 (6.0; 9.3) months; P < 0.01). Combined treatment tolerability was satisfactory in all 100 % of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation